Bridging the Research-to-Practice Gap Through Effective Professional Development for Teachers Working With Students With Emotional and Behavioral Disorders. (February 2019) - State, Talida M.; Simonsen, Brandi; Hirn, Regina G.; Wills, Howard
Students with emotional and behavioral disorders (EBD) experience a variety of externalizing and internalizing behavior problems, gaps in academic achievement, and increased rates of dropping out of school. Thus, it is essential that students with EBD receive evidence-based academic and behavioral supports from skilled and knowledgeable teachers to improve student outcomes. Unfortunately, teachers typically receive limited professional development in classroom management practices and other supports targeting the unique needs of students with EBD. In this manuscript, we describe (a) challenges in the field related to supporting students with EBD, (b) current practices in professional development, (c) a multitiered-system-of-support framework for organizing and providing professional development, and (d) the need for more research on efficient and effective professional-development supports for teachers of students with EBD.